Urinary Incontinency in Women in Uyo Metropolis, South-South, Nigeria - Udokang, N. E; Inyang, O. I.; Dick, S. F. (European Journal of Sustainable Development, 2016)
This study was a cross sectional study which examined urinary incontinence in women within Uyo metropolis of Akwa Ibom State, Nigeria. The survey was carried out among women within the ages of 16-75 years. Questionnaire was the instrument used for data collection and total sample of 254 women were selected using simple random sampling univariate association between the demographic characteristics of the subject. Urinary incontinence was examined using Chi-Square Test and multiple variate association was tested using multiple logistic regression. Results showed that Prolong Labour (OR = 3.01, C.I = 1.545 – 6.80, P<0.05), Episiotomy (OR = 1.82, C.I = 1.547- 5.001), Vaginal Infection (OR = 3.08, C.I = 1.544-10.899) and High Birth Weight (OR = 2.66, C.I = 1.961-7.370) were the factors were significantly associated with urinary incontinency in women. Hence, it could be concluded that prolong labour, episiotomy, vaginal infection and high birth weight babies are significantly related to urinary incontinence in women. Keywords: Urinary-incontinence; Episiotomy; Women; Infection; Labour